Variants in RHOBTB2 associated with cancer and rare developmental and epileptic encephalopathy - Solano, Elaina; Foksinska, Aleksandra; Crowder, Camerron M. (Frontiers in Pediatrics, 2024)
RHOBTB2 is a member of the Rho GTPases subfamily of signaling proteins, known tumor suppressors whose loss of function and decreased expression is associated with cancer onset. Beyond its cancer-related role, RHOBTB2 is implicated in rare neurodevelopmental disorders, specifically RHOBTB2-related disorders, recognized in 2018 as a subtype of developmental and epileptic encephalopathies (DEE). Common symptoms of these disorders include early-onset epilepsy, severe intellectual disability, microcephaly, and movement disorders. Few studies have investigated patient variants associated with RHOBTB2-related disorders, and the impact of these variants on protein function remains unclear. Limited research suggests that the accumulation of RHOBTB2 in neural tissues contributes to the development of DEE. Similarly, preclinical studies indicate that missense variants near or in the BTB domain of RHOBTB2 result in decreased degradation of RHOBTB2 and the onset of DEE, whereas variants in the GTPase domain cause more variable neurodevelopmental symptoms, but do not impair proteasomal degradation of RHOBTB2. However, the exact pathophysiological mechanisms are unclear and may differ across variants. Current treatment approaches for individuals with RHOBTB2-related DEE involve the use of antiseizure medications to decrease seizures; however, no treatments have been identified that address the other symptoms or the underlying pathophysiological mechanisms associated with these disorders. Overall, RHOBTB2 remains an understudied protein with limited information on its function and how it contributes to disease mechanisms. This review provides an overview of the current knowledge of RHOBTB2 function, with an emphasis on its association with neurodevelopmental disorders through an analysis of preclinical studies and case reports that link individual variants with clinical features.